Management Of Inclusive Education Services In Enhancing School Competitiveness - Januariani; Ahmad Tanzeh; Akhyak (International Journal of Education Management and Religion, 2026)
This study examines the management of inclusive education services as a strategic approach to enhancing school competitiveness in primary schools and madrasah ibtidaiyah in Tulungagung, Indonesia. Employing a qualitative multi-case study design, the research was conducted at SD Muhammadiyah 1 Tulungagung, SDI Al Azhaar Tulungagung, and MI Modern SAKTI Permatahati Ibu Tulungagung. Data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, inclusion coordinators, Special Assistant Teachers, classroom teachers, and parents. Data analysis followed an interactive model consisting of reduction, display, and cross-case thematic verification. The findings reveal a coherent managerial cycle comprising needs analysis, integrated planning, consistent implementation, and continuous evaluation. Early identification and institutional readiness assessment ensure precise service alignment. Planning integrates individualized education programs, teacher professional development, and structured parental collaboration. Implementation operationalizes curriculum adaptation, therapeutic support, and inclusive participation in flagship programs. Evaluation mechanisms generate feedback loops that sustain service innovation and organizational learning. The study proposes a conceptual framework linking inclusive service management to student achievement, public trust, and institutional differentiation. Inclusive education management emerges not only as a rights-based obligation but also as a strategic driver of sustainable school competitiveness grounded in service quality and reputational capital.